Electronic Imaging & the Visual Arts. EVA 2014 Florence - Vito Cappellini (Firenze University Press, 2014)
Information Technologies of interest for Culture Heritage are presented: multimedia systems, data-bases, data protection, access to digital content, Virtual Galleries. Particular reference is reserved to digital images (Electronic Imaging & the Visual Arts), regarding Cultural Institutions (Museums, Libraries, Palace - Monuments, Archaeological Sites). The International Conference includes the following Sessions: Strategic Issues; EC Projects and Related Networks & Initiatives; 2D - 3D Technologies and Applications; Virtual Galleries - Museums and Related Initiatives; Access to the Culture Information. Three Workshops regard: International Cooperation; Innovation and Enterprise; e.Culture Cloud.